Human-Animal Relationship in an Anthropocene Era - Gautam, Dr (Literary Studies, 2020)
"How we treat our fellow creatures is only one more way in which each one of us, every day, writes our own epitaph-bearing into the world a message of light and life or just more darkness and death, adding to the world's joy or to its despair … Perhaps that is part of the animal's role among us, to awaken humility, to turn our minds back to mystery of things, and open our hearts to that most impractical of hopes in which all creation speaks as one." Matthew Scully, Dominion